Long-Term Effects of the Targeting the Ultra-Poor Program - A Reproducibility and Replicability Assessment of Banerjee et al. (2021) - Julian Rose; Florian Neubauer; Jörg Ankel-Peters (Institute for Replication (I4R), 2024)
Banerjee, Duflo, and Sharma (BDS, 2021a) conduct a ten-year follow-up of a randomized transfer program in West Bengal. BDS find large effects on consumption, food security, income, and health. We conduct a replicability assessment. First, we successfully reproduce the results, thanks to a perfectly documented reproduction package. Results are robust across alternative specifications. We furthermore assess the paper's pre-specification diligence and the reporting in terms of external and construct validity. While the paper refers to a pre-registration, it lacks a pre-analysis plan. Assessing the validity of findings for other contexts is difficult absent necessary details about the exact treatment delivery.
Keywords: A1; O12; 330; replicability; randomized controlled trial; transfer programs; research transparency